The interactive effect of facial appearance and behavior statement on trust belief and trust behavior. (15th October 2017) - Li, Tingni; Liu, Xinge; Pan, Junhao; Zhou, Guomei
Abstract: We investigated the interactive effect of facial appearance and reputation based on past behavior on trust belief and trust behavior in a one-shot standard Trust Game with Chinese participants. The faces and behavioral statements of partners were sequentially displayed to the participants. The participants had to evaluate the partners' perceived trustworthiness and decide how much money they would invest, as well as how much money they would expect the counterpart to return. The results showed that the Chinese participants' economic decisions were influenced by partner facial appearance. We also found an interactive effect of facial appearance and behavioral statements, and a significant interaction of sequence and behavioral statements. Behavioral statements alone had an effect on perceived trustworthiness only when they were shown first, but they had no effect when the faces were displayed first. Behavioral statements had an effect only through their interaction with the faces. However, faces can affect perceived trustworthiness alone, regardless of sequence. Finally, we proposed a model for illustrating the relationships among facial appearance, behavioral statements, perceived trustworthiness, investment amount, and the amount of expected return. Highlights: Chinese trust decision is influenced by partner's facial/behavioral information. Facial information takes effect when shown before/after behavioral information. Behavioral information only has an effect when shown before facial information. A SEM model is proposed to understand the internal mechanism.